THE GENERAL ELECTION OF WALI NANGGROE OF ACEH WITHIN REGIONAL HEAD ELECTION REGIME - Zulfiani Zulfiani; Fatimah Fatimah; Muhammad Ridwansyah (Universitas Syiah Kuala, 2022)
The objectives of this research are to examine how Article 70 paragraph (1) of Aceh Qanun Number 8, 2012 stipulates the formation of the Wali Nanggroe Election Commission through a process of deliberation and consensus, following democratic principles. and to analyze the characteristics of an ideal Wali Nanggroe Aceh election system, as it pertains to the Regional Head Election Regime. The research methodology employed in this study is normative legal research, utilizing a qualitative approach. The provision stated in Article 96 paragraph (4) of the aforementioned law serves as a safeguard for the distinctiveness and prerogatives of Aceh, as well as the electoral process for the position of Wali Nanggroe Aceh, which aligns with the principles outlined in Article 18B paragraph (1) of the 1945 Constitution. The findings are the selection process for the period of office of Wali Nanggroe should adhere to a pattern of specificity and privilege, while still respecting the principles underlying the establishment of the Wali Nanggroe position, even within the framework of the regional head regime. The regionalization of Wali Nanggroe's tenure should be implemented alongside respected leaders of society in Aceh, to provide a comprehensive and systematic accommodation of all segments of the Acehnese society.